(untitled) (Texas Journal of Medical Science, 2023)
The article highlights the priority areas of preventive pediatrics related to the formation of the health of the younger generation, the organization of medical care for children, and the reduction of morbidity, disability and mortality. The importance of vaccination in the control of the most widespread infections was noted, and the need to create a system for providing comprehensive rehabilitation care to disabled children was substantiated.